Numerous Vascular Malformations in Orofacial Region – A Diagnostic and Therapeutic Challenge - Debasish Pramanick (Journal of Orofacial Research, 2021)
Vascular lesions always remain a challenge as far as its diagnosis and treatment are concerned because of its close proximity to vital structures and risk of severe hemorrhage. Different types of vascular lesions like hemangiomas, vascular malformations are often encountered in day-to-day dental practice, but presence of multiple vascular lesions in the orofacial region is quite rare. Here, a rare and interesting case of multiple vascular malformations in the head-neck region of a 39-year-old female patient involving the tongue, cheeks, lips, palate and eyes has been reported. After getting prior informed consent and routine preoperative haematological investigations, an incisional biopsy was done from the buccal mucosal lesion and tongue lesion. Histopathological examination of the biopsied samples revealed the presence of non-dysplastic, parakeratinized stratified squamous epithelium backed by connective tissue stroma. The stroma contains numerous vascular channels containing red blood corpuscles within. No active endothelial proliferation was noted. Sprinkling of chronic inflammatory cells was also noted. Based on the said histopathological features, a diagnosis of vascular malformation was confirmed. Proper diagnosis and making differentiation between haemangiomas and vascular malformations is utmost important because of their different treatment plan.